Case Studies in Paleoethnobotany : Understanding Ancient Lifeways Through the Study of Phytoliths, Starch, Macroremains, and Pollen - Pearsall, Deborah M. (Routledge, 2018)
Cover -- Title -- Copyright -- Dedication -- Contents -- List of figures -- List of tables -- Preface -- Acknowledgments -- Part I The Nature and Study of Paleoethnobotanical Remains -- 1 Paleoethnobotanical Remains -- Introduction: The Paleoethnobotanical Approach -- Paleoethnobotanical Data and Their Study -- Macroremains -- Pollen -- Phytoliths -- Starch -- Studying Archaeobotanical Remains -- The Comparative Collection -- 2 Deposition and Preservation of Paleoethnobotanical Remains -- Introduction -- Macroremain Deposition and Preservation -- Summary -- Grinding Stone Example -- Phytolith Deposition and Preservation -- Summary -- Grinding Stone Example -- Starch Deposition and Preservation -- Summary -- Grinding Stone Example -- Pollen Deposition and Preservation -- Summary -- Grinding Stone Example -- Conclusion: Deposition and Preservation of Paleoethnobotanical Remains -- 3 Field Sampling and Recovery -- Introduction -- Strategies and Techniques for Sampling -- Flotation and Fine-Sieving -- Flotation Example: Using a SMAP-Style System -- Collecting Artifacts and Residues for Starch (and Other Microfossil) Analysis -- Guidelines for Selecting Artifacts -- Field-Sampling of Residues for Microfossil Study -- 4 Approaches to Paleoethnobotanical Interpretation -- Introduction -- Qualitative Analysis -- Quantitative Analysis -- Common Measures Used to Interpret Archaeobotanical Data -- Raw Data Tabulation -- Ubiquity/Percentage Presence -- Ratios -- Diversity -- Application of Multivariate Techniques -- Reading a Stratigraphic Diagram -- Part II Interpreting Paleoethnobotanical Data: Case Studies -- 5 Investigating Neanderthal Lifeways Through Paleoethnobotany -- Introduction -- Background to the Case Study -- Neanderthal Diet(s): The Contribution of Plant and Animal Foods -- Neanderthals as Top Predators: Faunal and Isotope Evidence.